2018
DOI: 10.1371/journal.pone.0191955
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes in hematological malignancies treated with haploidentical or HLA-identical sibling hematopoietic stem cell transplantation following myeloablative conditioning: A meta-analysis

Abstract: PurposeHaploidentical and human leukocyte antigen (HLA)-identical sibling hematopoietic stem transplantation are two main ways used in allogeneic hematopoietic stem cell transplantation (allo-HSCT). In recent years, remarkable progress has been made in haploidentical allo-HSCT (HID-SCT), and some institutions found HID-SCT had similar outcomes as HLA-identical sibling allo-HSCT (ISD-SCT). To clarify if HID-SCT has equal effects to ISD-SCT in hematologic malignancies, we performed this meta-analysis.MethodsRele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…The results of our meta-analysis are not in complete agreement with those of Chen et al [55] who compared the outcomes of patients who received MA with either a haplo-SCT or a matched-SCT from a MRD. These authors suggest that matched-SCT should be preferred over haplo-SCT, because they found lower rates of platelet engraftment, higher risk of acute GVHD, and worse overall survival and disease-free survival among the haplo-SCT groups.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The results of our meta-analysis are not in complete agreement with those of Chen et al [55] who compared the outcomes of patients who received MA with either a haplo-SCT or a matched-SCT from a MRD. These authors suggest that matched-SCT should be preferred over haplo-SCT, because they found lower rates of platelet engraftment, higher risk of acute GVHD, and worse overall survival and disease-free survival among the haplo-SCT groups.…”
Section: Discussioncontrasting
confidence: 51%
“…However, the haplo-SCT groups had a lower relapse rate and similar rates of neutrophil engraftment, chronic GVHD, and transplant-related mortality. The study by Chen et al [55] assessed 7 studies, 4 of which were included in our metaanalysis, that enrolled a total population of 1919 patients. We suspect that our larger population of over 11,000 patients allowed us to determine more accurate pooled effects for acute GVHD and relapse-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a literature search and found an additional 11 cases with BCR-FGFR1 rearrangement treated with allogeneic HSCT (Table 1), and to our knowledge, this case is the first report of a patient with a BCR-FGFR1 MPN treated with haploidentical HSCT. Haploidentical donors allow patients who lack a HLA-matched one to receive a HCST with outcomes which are much like those obtained with matched donors [21]. HSCT may be the only therapeutic option for long-term survival at least until more efficacious TKIs become available.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, studies by others (36, 112, 113, 115) and us (109, 111) have suggested the inferiority of MSDT to haplo-SCT, indicating that, for AML patients with positive pre-MRD and HL, haploidentical donors might be selected first in experienced centers, although controversy remains. Therefore, a prospective, randomized study is needed to elucidate which one has better anti-leukemia activity, MSDT or haplo-SCT?…”
Section: Recent Advances In the Beijing Protocolmentioning
confidence: 90%
“…Here, we summarize the advances in inducing T cell tolerance by treating healthy donors with G-CSF. We discuss the recent advances in the Beijing Protocol mainly focusing on strategies that have been used for poor graft function (PGF) (2630), virus infections (3133), and relapse (3436). We also indicate the application of G-CSF-primed allografts for other haploidentical allograft modalities.…”
Section: Introductionmentioning
confidence: 99%